فاعلية برنامج اليكتروني تكيفي وفقا للذكاءات المتعددة في تنمية مهارات البرمجيات الإحصائية - حسانين، ابتسام أحمد محمد; محمد، عزة محمد عبدالسميع; صالح، محمود مصطفى عطية (جامعة عين شمس - كلية التربية - مركز تطوير التعليم الجامعي, 2023)
هدف البحث الحالي إلى الكشف عن فاعلية البرنامج الإلكتروني التكيفي وفقا للذكاءات المتعددة في تنمية مهارات برمجيات الإحصاء وأثرة على تنمية متعة التعلم، وتكونت عينة البحث من (30) تلميذا من مدرسة الدكتور مصطفي كمال حلمي بمحافظة القاهرة الدكتور مصطفي كمال حلمي بمحافظة القاهرة دارة شرق مدينة نصر التعليمية، تم تقسيمهم إلى مجموعتين متساويتين تجربتين، كما اعتمد البحث على المنهج شبه التجريبي ذو المجموعتين مستخدما الأساليب الإحصائية اللابارمترية. وأسفرت النتائج عن:- "توجد فروق ذات دلالة إحصائية عند مستوي (0.05) بين متوسطات رتب درجات المجموعة التجريبية الأولي التي تعرضت (لنمط الذكاء الرياضي) في كل من القياسين القبلي والبعدي في اختبار مهارات البرمجيات الإحصائية لصالح القياس البعدي.- توجد فروق ذات دلالة إحصائية عند مستوي (0.05) بين متوسطات رتب درجات المجموعة التجريبية الثانية التي تعرضت (لنمط الذكاء المكاني) في كل من القياسين القبلي والبعدي في الاختبار مهارات البرمجيات الإحصائية لصالح القياس البعدي.- توجد فروق ذات دلالة إحصائية عند مستوي (0.05) بين متوسطات درجات المجموعة التجريبية الأولي والمجموعة التجريبية الثانية في القياس البعدي في الاختبار.- توجد فروق ذات دلالة إحصائية عند مستوي (0.05) بين متوسطات درجات المجموعة التجريبية الأولي في كل من القياسين القبلي والبعدي في مقياس متعة التعلم لصالح القياس البعدي.- توجد فروق ذات دلالة إحصائية عند مستوي (0.05) بين متوسطات درجات المجموعة التجريبية الثانية في كل من القياسين القبلي والبعدي في مقياس متعة التعلم لصالح القياس البعدي.- لا توجد فروق ذات دلالة إحصائية عند مستوي (0.05) بين متوسطات درجات المجموعة التجريبية الأولي والمجموعة التجريبية الثانية بعد تطبيق مقياس متعة التعلم. The objective of the current research is to reveal the effectiveness of the adaptive e-software according to the multiple smarts in the development of statistical software skills and the impact on the development of learning pleasure. The research sample consisted of (30) Pupils from Dr. Mustafa Kamal Hilmi School in Cairo governorate Dr. Mustafi Kamal Hilmi in Cairo governorate Dara east of Nasr Educational City were divided into two equal experimental groups. The research also relied on the semi-experimental two-group curriculum using paralympic statistical methods. The results resulted in:- There are statistically significant differences at a level (0.05) between the grade averages of the initial experimental group exposed (for mathematical intelligence pattern) in both tribal and post measurements in the statistical software skills test in favor of dimensional measurement.- there are statistically significant differences at the level (0.05) between the second experimental group grade averages that have been exposed (for spatial intelligence pattern) in both tribal and post-test measurements statistical software skills in favor of dimensional measurement.- There are statistically significant differences at a level (0.05) between the initial experimental group score averages and the second experimental group in the test dimensional measurements. - Statistically significant differences exist at a level (0.05) between the initial experimental group score averages in both tribal and post measurements in the learning pleasure scale in favour of the dimensional measurement. - Statistically significant differences exist at a level in the second empirical group (0.05) 0.05) between the first and second pilot group score averages after applying the learning pleasure scale.
Keywords: التعليم الأساسي -- التعليم الإلكتروني -- مهارات الحاسب الآلي -- الذكاءات المتعددة